HOW DOES STUDENTS MOTIVATION TO ACQUIRE NEW GEOSPATIAL SKILLS INFLUENCE THEIR CHOICES OF E-LEARNING CONTENT? - Aneta Szablowska-Midor; Natalia Kolecka; Jacek Kozak; Krzysztof Ostafin (European Journal of Geography)
Higher education in many disciplines is affected nowadays by an evident orientation to assist students in developing a certain set of skills required by the labour market. This trend is visible also in the field of Geographic Information Science and Technology (GIS&T). The composition of competencies encompasses, apart from industry-specific technical competencies, also soft skills related to personal effectiveness, academic and workplace competencies. Moreover, soft skills are gaining in importance, being identified as future work skills. As a result, students may search for certain skills when they come into contact with a particular learning content. In this study, we investigated how the motivation to acquire specific skills influences students’ behaviour on the e-learning platform. As a case study, we selected a study programme in land management carried out at the Institute of Geography and Spatial Management (Jagiellonian University in Cracow, Poland). Several different motivating factors, like GIS&T skills and the ability to co-operate, were identified and compared with students’ behaviour on the e-learning platform in certain modules of the study programme. The results indicated that students only partially prospected for certain competencies during their work with the content of the e-learning platform. Students’ motivation was more evident in their online behaviour when they wanted to acquire technical skills than when they planned to develop soft skills.